An electro-pneumatic active vibration control system for the driver's seat of agricultural tractors - STEIN, G.J. (Archives of Acoustics, 1996)
The aim of this contribution is to present some results of the study of driver's seat with an electro-pneumatic active vibration control system applied for driver's seats of agricultural wheeled tractors. The actuator is parallel to the conventional pneumatic seat suspension and a proportional electro-pneumatic valve is used as the control element. The description of the full scale dummy system is augmented by a short theoretical description of the 1 DOF model of this system and by some results of measurements on a laboratory vibration simulator. The seat vibration control properties are evaluated according to the ISO Standard 5007:1990 pertinent to evaluation of seats for agricultural wheeled tractors.